Groupware sebagai Salah Satu Teknologi Informasi untuk E- Learning (Distance Learning) - Julisar, Julisar (ComTech: Computer, Mathematics and Engineering Applications, 2013)
E-Learning is the process of distance learning by using of computer technology, computer network and/or Internet. E-Learning is delivered by utilizing computing devices. With e-learning, lecture material can be distributed either on-line using a network connection as well as off-line using a mobile media. One type of software used in distance learning is Groupware. It is a software product to support a group of people who share a task or goal to work together to achieve that goal. Two types of groupware technology are Electronic Teleconferencing and Real-time Collaboration Tools. Electronic Teleconferencing is electronic communication technology that allows two or more people in different locations to simultaneously conduct the conference. In Video Conference, participants in a location can see the other participants who are in different locations.